Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter 10 - Section 10.1 - Sequences and Summation Notation - Exercise Set: 7

Answer

-4,5,-6,7

Work Step by Step

To find the first four terms of the sequence whose general term is $a_{n}$ = $(-1)^{n}$(n+3), we replace n in the formula with 1,2,3, and 4. n=1, $a_{1}$ = $(-1)^{1}$(1+3) = -1 * 4 =-4 n=2, $a_{2}$ = $(-1)^{2}$(2+3) = 1* 5=5 n=3, $a_{3}$ = $(-1)^{3}$(3+3) = -1 *6 = -6 n=4,$a_{4}$ = $(-1)^{4}$(4+3) = 1 *7 = 7 The first four terms are -4,5,-6,7.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.